Implementation of Academic Supervision by the Principal of Mas Al-Baqiyatussholihat Cibarusah Bekasi - Siti Khoeriyah; Ajat Rukajat; Muchdjabir Wahid (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to analyze the implementation of academic supervision conducted by the principal at MAS Al-Baqiyatussholihat Cibarusah Bekasi, which includes the aspects of planning, implementation, evaluation, and follow-up of academic supervision in improving teacher professionalism and the quality of learning. This study employed a qualitative approach using a descriptive case study method. Data were collected through interviews, observations, and documentation involving the principal, teachers, and students as research participants. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that academic supervision at MAS Al-Baqiyatussholihat has been implemented however, it has not yet been carried out optimally. In the planning aspect, academic supervision has been administratively available but has not been systematically and structurally organized. The implementation of supervision remains incidental and focuses more on administrative inspection rather than direct classroom observation. Evaluation of supervision is conducted through verbal feedback, yet it lacks systematic documentation. Furthermore, follow-up actions have been carried out through workshops and seminars, but they are not fully based on systematic supervision evaluation results. Therefore, strengthening a more planned, sustainable, and structured academic supervision system is necessary to improve teacher professionalism and the quality of learning.